2018
DOI: 10.3390/cancers10090313
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Assessment of Lactate Production and Compartmentalization in Renal Cell Carcinomas Using Hyperpolarized 13C Pyruvate MRI

Abstract: Optimal treatment selection for localized renal tumors is challenging due to their variable biological behavior and limited ability to pre-operatively assess their aggressiveness. We investigated hyperpolarized (HP) 13C pyruvate MRI to noninvasively assess tumor lactate production and compartmentalization, which are strongly associated with renal tumor aggressiveness. Orthotopic tumors were created in mice using human renal cell carcinoma (RCC) lines (A498, 786-O, UOK262) with varying expression of lactate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…For in vivo studies, the HP [1-13 C]lactate that effluxes out of the cell will remain predominately in the tumor microenvironment and should add rather than subtract from the HP [1-13 C]lactate signal, providing a large increase in hyperpolarized lactate with the presence of Gleason grade 4 and 5 cancer. This supposition is consistent with prior studies involving renal cell cancer cells implanted under the renal capsule [49]. The ability to assess the percentage of Gleason grade 4 and 5 cancer in a tumor has significant implications for selection of the appropriate therapy for patients since cancers with a Gleason score of ≤ 3 + 3 are considered indolent and appropriate for active surveillance while a Gleason score of 7 or higher portends more aggressive cancer.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For in vivo studies, the HP [1-13 C]lactate that effluxes out of the cell will remain predominately in the tumor microenvironment and should add rather than subtract from the HP [1-13 C]lactate signal, providing a large increase in hyperpolarized lactate with the presence of Gleason grade 4 and 5 cancer. This supposition is consistent with prior studies involving renal cell cancer cells implanted under the renal capsule [49]. The ability to assess the percentage of Gleason grade 4 and 5 cancer in a tumor has significant implications for selection of the appropriate therapy for patients since cancers with a Gleason score of ≤ 3 + 3 are considered indolent and appropriate for active surveillance while a Gleason score of 7 or higher portends more aggressive cancer.…”
Section: Discussionsupporting
confidence: 79%
“…One approach for estimating lactate efflux in vivo is based on the concept that the compartmental (intra-versus extra-cellular) difference in mean free diffusion path length would be reflected by the apparent diffusion constant (ADC). While the clinical feasibility of measuring HP lactate ADC is still under development, there are numerous preclinical studies that have shown that it can be measured and used to stratify tumor aggressiveness [49,[55][56][57][58][59]].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to the lower cell density of the A498 tumors contributing to the lactate signal (for the same voxel volume). Prior work in Sriram et al 16 has demonstrated that cellular density and proton ADC are inversely correlated (cellular density ~ 1/ADC) for these RCC tumors. Thus, using the same rationale and data, cell density‐normalized k PL values can be calculated by using the k PL x ADC product.…”
Section: Resultsmentioning
confidence: 88%
“…In tissues, automated cell counting and/or protein quantification requires tissue digestion, making it impossible to obtain high‐quality histopathology. It is possible to estimate tissue cellularity using automated image analysis of histopathology slides; however, given the heterogeneity of human prostate tissue, this approach might yield inaccurate results unless the fixed, embedded, and stained tissue is comprehensively sliced to yield a 3D image stack. Another possibility is to analyze the metabolites of interest in terms of their ratios to a reference metabolite .…”
Section: Discussionmentioning
confidence: 99%